Optical aspects and energy performance of switchable ethylene-tetrafluoroethylene (ETFE) foil cushions - Flor, Jan-Frederik; Liu, Dingming; Sun, Yanyi; Beccarelli, Paolo; Chilton, John; Wu, Yupeng (Elsevier, 2018)
A pneumatic multilayer foil construction with a kinetic shading mechanism has the potential to be an effective response to dynamic climatic factors, such as solar radiation, and therefore moderate the energy consumption of buildings. A parametric study was carried out on a switchable ethylene-tetrafluoroethylene (ETFE) foil cushion with the purpose of investigating the optical performance of an adaptive building envelope and its impact on building energy performance regarding heating, cooling and lighting. Ray-tracing techniques were used to investigate the effects of surface curvature, frit layout and frit properties, on the optical performance of the cushion in open and closed mode. A range of incidence angles for solar radiation were simulated. The results of the simulation showed an angle dependent optical behaviour for both modes. The influence of the dynamic shading mechanism on building energy performance was further evaluated by integrating the optical data obtained for the ETFE foil cushions in a comprehensive energy simulation of a generic atrium building using EnergyPlus. Results suggested that switchable ETFE foil cushions have a higher potential to reduce cooling and heating loads in different climatic regions, compared to conventional glazing solutions (i.e. uncoated double-glazing and reflective double-glazing), while providing good conditions of natural daylighting. Annual energy savings of up to 44.9% were predicted for the switchable ETFE foil cushion in comparison to reflective double glazing. As such, this study provides additional insight into the optical behaviour of multilayer foil constructions and the factors of design and environment that potentially have a major impact on buildings energy performance.